Cihan harbinde deniz muharebeleri ve İskajerak - Kurtoğlu, Hüseyin Fevzi, 1890-1945. (İstanbul)
2 cilt (1. c. [1], 1, 13-16, 114 sayfa, [24] sayfa resim, portre, çizim, harita, tablo ; 2. c. sayfa [115]-343, [46] sayfa resim, harita, plan)